DETERMINANTS OF RISK REPORTING : EVIDENCE FROM INDONESIA - Fujianti, Lailah; Florida Aryani; Amelia Damayanti (Dinasti Publisher, 2020)
This study analyzes risk reporting determinants namely the board of commissioners, independent commissioner and audit committee. The sample of this study consisted of 34 companies listed on the Indonesia Stock Exchange (IDX) and submitted the annual financial reports to the Indonesia Stock Exchange in 2015 and 2016. The test results showed that the board of commissioners and independent commissioners had an effect on risk disclosure, while the audit committee had no effect against risk reporting.